Lymph node metastasis characteristics of papillary thyroid carcinoma located in the isthmus: A single-center analysis. Issue 24 (June 2017) - Li, Genpeng; Lei, Jianyong; Peng, Qian; Jiang, Ke; Chen, Wenjie; Zhao, Wanjun; Li, Zhihui; Gong, Rixiang; Wei, Tao; Zhu, Jingqiang
Abstract : Abstract: The frequency and pattern of lymph node metastasis and the extent of dissection for isthmic papillary thyroid carcinoma (PTC) remain unclear, and the aim of this present study was to evaluate these characteristics and to attempt to detect the best surgical protocol for isthmic PTCs. A total of 3185 consecutive patients with PTCs were reviewed. Of these patients, 47 with a single isthmic PTC were enrolled in our study, and matched 47 patients with a single PTC located in the unilateral lobe were randomly selected and added for comparison of their baseline tumor characteristics and lymph node metastasis characteristics. Univariate and multivariate analyses were performed to determine the risk factors for central lymph node metastasis in PTCs. The isthmic PTCs showed a higher rate of capsule invasion ( P = .013) and advanced pathological N stage ( P = .038) compared to the PTCs located in the lobe; meanwhile, pathological evidence of central lymph node metastasis ( P = .040) was more frequent in the isthmic PTC group than in the control group. The univariate and multivariate analyses indicated that the tumors located in the isthmus (hazard ratio [HR]: 2.769; 95% confidence interval [CI]: 1.124–6.826; P = .027) and those with advanced (T2–4) pathological classifications (HR: 4.282; 95% CI: 1.224–14.976; P = .023) were independent risk factors for central lymph node metastasis in PTC patients. Due to the higher rate of pathological central lymph node metastasis and independent risk factors for central lymph node metastasis, total thyroidectomy, and bilateral central lymph node dissection should be considered the standard surgical protocol for isthmic PTCs.